CH2 - Polynomials and Polynomial Equationsss

Download as docx, pdf, or txt
Download as docx, pdf, or txt
You are on page 1of 15

CHAPTER II.

Polynomials and Polynomial Equations

Lesson 1. Long Division and Synthetic Division

Lesson 2. Remainder Theorem

Lesson 3. Factor Theorem

Lesson 4. Rational Root Theorem

Lesson 5. Factoring Polynomials

Lesson 6. Polynomial Equations

OBJECTIVES

At the end of this chapter, you should be able to:

a. perform division of polynomials using long division and synthetic division,

b. illustrate and prove the Remainder Theorem, Factor Theorem and the Rational Root Theorem,

c. factor polynomials,

d. illustrate polynomial equations; and,

e. solve problems involving polynomials and polynomial equations


Lesson 1. Long Division and Synthetic Division

1.1. Long Division or Division Algorithm


Division algorithm is the division process that you are familiar with. Dividing polynomials are
the same as dividing numbers.
All you have to do is to follow the steps in dividing a polynomial by another polynomial as
illustrated in the example below.

EXAMPLE Divide:

( – x2 + 3x3 - 8x + 5) by (x + 2) Steps

(3x3 - x2 - 8x + 5) by (x + 2) 1. Arrange the terms of the dividend


and divisor according to degree.
3x2
x + 2 3x3 - x2 - 8x + 5 2. Divide the first term of the
dividend by the first term of the divisor
to get the first term of the quotient.
3x2
x + 2 3x3 - x2 - 8x + 5 3. Multiply the result in step 2 by the
3x3 + 6x2 divisor.

3x2 -7x 4. Subtract the result from step 3.


x + 2 3x3 - x2 - 8x + 5 Bring down the next term of the
3x3 + 6x2 dividend.
- 7x2 - 8x

3x2 - 7x + 6 5. Repeat the entire process using


x + 2 3x3 – x2 - 8x + 5 the result in step 4 as the new
3x3 + 6x2 dividend.
- 7x2 - 8x
- 7x2 -14x 6. Express the result as:
6x + 5
6x +12 dividend = quotient + remainder
-7

3x3 – x2 - 8x + 5 = 3x2 – 7x + 6 - 7
x+2 x+2

The quotient of – x2 + 3x3 - 8x + 5 by x + 2 is 3x2 – 7x + 6 and the remainder is -7.

TRY THIS Divide x3 – 13x + 12 by (x + 4).


1.2. Synthetic Division
Another method that is widely used is synthetic division. Unlike the usual division
which involves the four fundamental operations, this method requires only addition and multiplication
applied to the coefficients. This method is applied when the divisor is of the form x - c.

Steps to follow in dividing by synthetic division:

1. Arrange the terms of the dividend in descending order of exponent.


2. Write the numerical coefficient in a row, with 0 representing any missing term.
3. Write the constant term c of the divisor x - c at the left hand side of the of the coefficient.
4. Bring down the leading coefficient of the dividend. Multiply it by c and add to the second column.
5. Multiply the sum obtained in step 4 by c and add to the 3rd column. Repeat this process until you
reach the last column.
6. The 3rd rows of numbers are numerical coefficient of the quotient. The degree is one less than that
of the dividend. The right member is the remainder.
EXAMPLE P(x) = x3 + 4x2 + 3x – 2 by x – 3
SOLUTION x–3=0
x=3

1 4 3 -2
3 3 21 72
2 70
1 7 24 70 Thus, the quotient is x + 7 x +24 +
x −3

TRY THIS Find the quotient of 3x 4 – 2x3 + 5x 2 – 4x – 2 when divided by 3x + 1

EXAMPLE Divide ( – x2 + 3x3 - 8x + 5) by (x + 2)

SOLUTION 3 x 3 – x 2 – 8 x +5 x+2=0
x = -2

3 -1 -8 5
-2 -6 14 -12
2 7
3 -7 6 -7 Thus the quotient is 3 x – 7 x +6 – .
x +2

TRY THIS Divide 2x4 – 18x2 – 7 – x3 by x – 3.


EXERCISE 1

Name: ______________________________________________ Date: _______________

A. Find the quotient of the following using long division AND synthetic division.

1. Divide P(x) = 4x4 + 12x3 + 9x2 – 8x – 5 by 2x + 1

2. P(x) = 15x3 – 19x2 + 24x – 12 by 3x – 2

3. P(x) = -9x4 + 9x3 – 26x2 + 26x – 8 by 3x - 1


Lesson 2. Remainder Theorem
In the two previous division processes illustrated, a remainder was noted when the polynomial
is not exactly divisible by another polynomial. You’ll get a zero remainder when a polynomial is
exactly divisible by another.
By substituting the value of (c) of the divisor x – c in the polynomial P(x), you can also test
whether a certain polynomial is exactly divisible by another or is a factor by the Remainder Theorem.
The Remainder Theorem states that P(c) is the remainder when the polynomial P(x) is divided
by (x – c). The divisor x – c is then restated as x = c.

EXAMPLE Find the remainder using the remainder theorem if P(x) = x 3 + 4x2 + 3x – 2 is divided by
x – 3.
SOLUTION Instead of using synthetic division, it is easier to solve by substitution.

P(x) = x3 + 4x2 + 3x – 2; x = 3
P(3) = (3) + 4(3) 2 + 3(3) – 2 Substitute 3 for x.
= 27 + 36 + 9 – 2
P(3) = 70 the remainder
Hence, the polynomial P(x) = x3 + 4x2 + 3x – 2 is not exactly divisible by x – 3.

TRY THIS Find the remainder if ( – x2 + 3x3 - 8x + 5) is divided by (x + 2).

EXAMPLE Find the value of P(x) using the remainder theorem if P(x) = x 4 + 3x3 - 5x2 – 5x - 2 is
divided by x + 2.
SOLUTION P(x) = x4 + 3x3 - 5x2 – 5x - 2 ; x = -2
P(-2) = (-2) 4 + 3(-2) 3 - 5(-2) 2 – 5(-2) -2 Substitute -2 for x.
= 16 - 24 + 20 - 10 - 2
P(-2) = 0 the remainder x + 2 is a factor.

TRY THIS Find the value of P(x) = x3 + 4x2 + 3x – 2 when divided by x – 3.

EXAMPLE Find the value of P(x) = 2x4 – 18x2 – 7 – x3 when divided by x – 3 using Remainder
Theorem and Synthetic Division.
SOLUTION 2x4 – 18x2 – 7 – x3 , x – 3 = 0 ⇒ x = 3
Using Remainder Theorem,
P(3) = 2(3)4 – 18(3)2 – 7 – (3)3 Substitute 3 for x.
P(3) = -34
The remainder is -34.

Using Synthetic Division,


P(x) = 2x4– x3 – 18x2 – 7 Rewrite the function in descending order of degree.
x–3=0⇒x=3 Equate your divisor to 0.

2 -1 -18 0 -7
3 6 15 -9 -27
2 5 -3 -9 -34 – remainder x – 3 is not a factor.

TRY THIS Using Remainder Theorem and Synthetic Division, determine the value of
P(x) = (x3 – 7x2 + x + 10) when divided by x – 2.
EXERCISE 2

Name: ___________________________________________ Date:___________

A. Find the remainder when P(x) is divided by x – c using the remainder theorem.

1. (x) = (x4 + 10x3 - 8x –80) x + 10

2. P(x) = (x5 + 2x4 – 3x3 + 4x2 - 5x + 2) x–1

3. P(x) = (x3 + 3x2 + 10x + 5) x–3

B. Find the value of the following function using the remainder theorem.

1. p(x) = 2x3 - 5x2 + 3x -7


x = -3

2. p(x) = 5x3 + 7x2 + 8


x = -2

3. p(x) = 4x4 + 5x3 + 8x2


x=4
Lesson 3. Factor Theorem
In your experience with numbers, you obtain a remainder of zero when a number is exactly
divisible by another number. We can say that the divisor is a factor of the dividend in that case.
Same is true with polynomials.
A zero remainder obtained when applied using the Remainder Theorem will give rise to
another theorem called the factor theorem. This is a test to find if a polynomial is a factor of another
polynomial.
The Factor Theorem states:
Let P(x) be a polynomial. If c is a zero of P that is P(c) = 0, then (x - c) is a factor of P(x).
Conversely, if (x - c) is a factor of P(x) then, c is a zero of P.

Simply, if zero is obtained as a remainder when c is substituted to the polynomial P(x), then
the polynomial x – c is factor of P(x).***

EXAMPLE Show that x - 2 is a factor of x3 + 7x2 + 2x – 40


SOLUTION a. Using the remainder theorem

P(x) = x3 + 7x2 + 2x –40 if x = 2


= (2) 3 + 7(2) 2 + 2(2) – 40
= 6 + 28 + 4 - 40
P(2) = 0

Since P(x) = 0, then x - 2 is a factor of x3 + 7x2 + 2x – 40.


b. Using another method, by synthetic division

1 7 2 -40
2 2 18 40

1 9 20 0 the remainder

Since the remainder is 0, then x - 2 is a factor of x 3 + 7x2 + 2x –40.

TRY THIS Show whether x – 2 is a factor of x3 – 7x2 + x + 10.

EXAMPLE Determine if ( x – 3) is a factor of (2x4 - x3 – 18x2 – 7)


SOLUTION a. By remainder theorem
P(3) = 2x4 - x3 – 18x2 - 7 if x = 3
= 2(3)4 - (3)3 - 18(3)2 - 7
= 2(81) - 27 - 18(9) - 7
=162 –27 –162 – 7
P(3) = -34
Since the P(3) = -34, which is not 0 then, (x – 3) is not a factor of (2x 4 - x3 – 18x2 – 7).
b. Using synthetic division
2 -1 -18 0 -7
3 6 15 -9 -27

2 5 -3 -9 -34 remainder
Since r = -34, then x – 3 is not a factor of the second polynomial.

TRY THIS Determine whether (x – 2) is a factor of f(x) = 3x3 – 8x2 + 3x + 2.


EXERCISE 3

Name: _____________________________________________ Date: __________________

A. Determine if the second polynomial is a factor of the first polynomial.

1. P(x) = 2x4 + x3 + 2x + 1; (x + 1)

2. P(x) = x3 + 4x2 + x – 6; (x + 3)

B. Which of the following is a factor of (x) = x3 – 7x + 6.

a. x + 2

b. x – 3

c. x – 1

d. x + 1
Lesson 4. Rational Root Theorem
If f(x)= anxn + an-1xn-1 + …..+ a1x1 + a0 has integer coefficients, then every rational zero of f(x)
has the following form:
p factors of theconstant term a0
=
q factors of the leading coefficient a n

EXAMPLE Find all the possible roots of f ( x )=x 2 – 4 x+3 using Rational Root Theorem.
SOLUTION Factors of your constant term (p = 3) : ± 1, ± 3
Factors of the leading coefficient ( q = 1) : ± 1
1 3
Possible rational root: ± ,±
1 1
Simplified list: ± 1, ± 3

Using Remainder Theorem

x=1 x = -1 x=3 x = -3
2 2 2
f ( x )=x – 4 x+3 f ( x )=x – 4 x+3 f ( x )=x – 4 x+3 ( x )=x 2 – 4 x +3
f ( 1 ) =12 – 4(1)+3 f −1 ) =(−1)2 – 4 (−1)+ 3
( f ( 3 )=32 – 4 (3)+3 f (−3 )=(−3)2 – 4(−3)+3
f(x)= 0 f(x) = 8 f(x) = 0 f(x) = 24

Using Synthetic Division

1 -4 3 1 -4 3
1 1 -3 -1 -1 5
1 -3 0 1 -5 8

1 -4 3 1 -4 3
3 3 -3 -3 -3 21
1 -1 0 1 -7 24

Since 1 and 3 give the remainder of 0, thus the roots of are 1 and 3.

TRY THIS Find the factors of f ( x )=x 2 +7 x+ 12.

EXAMPLE Find the roots of the given function f ( x )=x 3−4 x 2−11 x +30.
SOLUTION Possible rational roots: ± 1, ± 2 ,± 3 , ±5 , ±6 ,± 10 , ±15 , ±30
Use any of these (Remainder Theorem, Factor Theorem, Synthetic Division) to find all
possible factors.

1 -4 -11 30 1 -4 -11 30
-1 -1 5 6 2 2 -4 -30
1 -5 -6 36 1 -2 -15 0

Since 2 gives a remainder of 0, that means 2 is one of the roots. (There are other
factors).
TRY THIS Find all the rational roots of the given function f(x) = x3 – x2 – 5x – 3.

EXERCISE 4

Name: _________________________________________________ Date:_________

A. Find all the possible roots of the given function:

a. f(x) = x3 + 4x2 + 3x – 2

b. p(x) = 3x3 + 2x2 – 7x + 2

c. g(x) = x3 – 2x2 – 5x + 6
Lesson 5. Factoring Polynomials
The zeros of a polynomial function can be determined easily if the polynomial is in factored
form. But the problem arises when the polynomial is expressed otherwise. The polynomial must be
factored (if it is factorable) using techniques learned in elementary algebra.

EXAMPLE Factor the given function f ( x )=x 3−4 x 2−11 x +30


SOLUTION Possible rational roots: ± 1, ± 2 ,± 3 , ±5 , ±6 ,± 10 , ±15 , ±30
If x = 2
1 -4 -11 30
2 2 -4 -30
1 -2 -15 0

Since the r = 0, that means (x - 2) is a factor and the other one is x 2 – 2 x−15 (quotient
in the synthetic division.) However, if the quotient in the synthetic division can still be
factored out, do so.
x 2 – 2 x−15
Possible rational roots: ± 1, ± 3 ,± 5 , ±15
If x = -3
1 -2 -15
-3 -3 15
1 -5 0
Since the r = 0, that means (x + 3) is also a factor. And the remaining is (x – 5).
Thus, f ( x )=x 3−4 x 2−11 x +30=( x−2 )( x +3 ) (x−5)

TRY THIS Factor the given function f(x) = x3 + 7x2 + 2x – 40.

EXAMPLE Factor g(x) = x4 – x3 – 11x2 + 9x + 18.


SOLUTION Possible rational roots: ± 1, ± 2 ,± 3 , ±6 , ± 9 ,± 18
If x = -1
1 -1 -11 9 18
-1 -1 2 9 -18
1 -2 -9 18 0
If x = 2
1 -2 -9 18
2 2 0 -18
1 0 -9 0
If x = -3
1 0 -9
-3 -3 9
1 -3 0
The factors are (x + 1)(x -2)(x +3) and the remaining quotient (x – 3).
Hence, g(x) = x4 – x3 – 11x2 + 9x + 18 = (x + 1)(x -2)(x +3)(x – 3).

TRY THIS Factor f(x) = x3 + 3x2 – 4x – 12


EXAMPLE Factor the following function
1. f(x) = x3 – 3x2 – 6x + 8
2. g(x) = x3 + 2x2 – 5x – 6
3. h(x) = x4 + 4x3 + x2 – 6x
SOLUTION
1. f(x) = x3 – x2 – 2x2 – 6x + 8 Using factoring by grouping.
3 2 2
= (x – x ) – (2x + 6x – 8)
= x2(x – 1) – 2(x2 + 3x – 4)
= x2(x – 1) – 2(x + 4)(x – 1)
= (x – 1)[x2 – 2(x + 4)]
= (x – 1)(x2 – 2x – 8)
= (x – 1)(x + 2)(x – 4)

2. g(x) = x3 + 2x2 – 5x – 6
g(x) = x3 + (x2 + x2) – 5x – 6 Using factoring by grouping.
= (x3 + x2) + (x2 – 5x – 6)
= x2(x + 1) + (x + 1)(x – 6)
= (x + 1)[x2 + (x – 6)]
= (x + 1)(x2 + x – 6)
= (x + 1)(x + 3)(x – 2)

3. h(x) = x4 + 4x3 + x2 – 6x

h(x) = x(x3 + 4x2 + x – 6) Using common monomial factoring


3 2 2
= x(x + 2x + 2x + x – 6) Factoring by grouping
= x[(x3 + 2x2) + (2x2 + x – 6)]
= x[x2(x + 2) + (x + 2)(2x – 3)]
= x{(x + 2)[x2 + (2x – 3)]}
= x[(x + 2)(x2 + 2x – 3)]
= x(x + 2)(x + 3)(x – 1)

TRY THIS Factor the following.

1. h(x) = x3 – x2 – 10x – 8
2. p(x) = x3 + 4x2 + x – 6
3. y = x3 + x2 – x – 1
EXERCISE 5

Name: _______________________________________ Date:____________

A. Determine the factors of the given function.

1. f(x) = x3 – 6x2 + 5x + 12

2. g(x)= x3 – 3x2 – 4x + 12

3. h(x) = x3 – 5x2 – 2x + 24
Lesson 6. Polynomial Equations
A rational integral equation of degree n in the variable x is an equation in the form
anxn + an-1xn-1 +…… + a1x + a0 = 0 , an ≠ 0 , where n is a positive integer and a0, a1, …., an are
constants. This expression is better known as polynomial equation.

EXAMPLES a. x 2+ 1=0
b. x 3 – 27=0
c. 2 x3 – 2 x +7=0
d. −x 4 – 1=0
e.5 x 4 +3 x 3 – 2 x=0

Solving Polynomial Equations


You already learned the factor theorem, remainder theorem and rational root theorem. Also,
the important methods – the synthetic division and long division. In solving polynomial equations, you
will need those knowledge.

EXAMPLE Find the value of x to satisfy the equation, x 3−4 x 2−11 x+30=0
SOLUTION Possible roots:± 1, ± 2 ,± 3 , ±5 , ±6 ,± 10 , ±15 , ±30
If x = 2
1 -4 -11 30
2 2 -4 -30
1 -2 -15 0

If x = -3 1 -2 -15
-3 -3 15
1 -5 0

If x = 5 1 -5
5 5
1 0

Thus, the values of x that will satisfy the given equation are 2, -3, and 5.

TRY THIS Find all the zeros of the equation x4 + 4x3 + x2 – 6x = 0.

EXAMPLE Solve for the roots of the polynomial equation x 4 – 16=0.


SOLUITON Note: All terms of the equation are perfect square. ( a 2 n – b2 n )=( a2 – b2 ) ( a 2+b 2 ),
where n is a positive number.
x 4 – 16=0
2
( x 2 ) – 4 2=0
( x 2 – 4 ) ( x 2+ 4 ) =0 Factor x 2 – 4 , since it is a perfect square.
( x – 2 )( x +2 ) ( x 2+ 4 )=0 Equate each factor to 0.
x – 2=0 x +2=0 x 2+ 4=0
x=2 x=−2 x 2=−4
x=± √−4
Thus the roots are, 2, -2, √ −4 , -√ −4 .
TRY THIS Find the roots of the equation x 3+ 2 x – x – 2=0.

EXERCISE 6

Name: _________________________________________________ Date:___________

A. Find the roots of the following polynomial equations.

1. –x^3 – x^2 – x -2 = 0 2. 2x^3 – 3x^2 – 11x + 6 = 0

2. 2x^4 – 3x^3 – 7x^2 – 8x + 6 = 0 4. 3x^2 + 2x^2 – 3x – 2 = 0

You might also like